End-point diagnostics of Giardia duodenalis assemblages A and B by combining RPA with CRISPR/Cas12a from human fecal samples - Yilin Wang; Fuchang Yu; Yin Fu; Qian Zhang; Jinfeng Zhao; Ziyang Qin; Ke Shi; Yayun Wu; Junqiang Li; Xiaoying Li; Longxian Zhang (Parasites & Vectors, 2024)
Abstract Background Giardia duodenalis is a common enteric protozoan parasite that is categorized into eight assemblages (A–H). In particular, assemblages A and B are zoonotic, capable of infecting both humans and animals worldwide, resulting in significant economic losses and public health challenges in epidemic regions. Thus, the development of rapid, accurate and non-laboratory-based diagnostic methods for infected animals is crucial for the effective prevention and control of giardiasis. Recent advancements in clustered, regularly interspaced, short palindromic repeats (CRISPR) and CRISPR-associated (Cas) protein (Cas12a) systems allow promising avenues for nucleic acid detection, characterized by their high flexibility, sensitivity and specificity. Methods Combined recombinase polymerase amplification and CRISPR/Cas12a systems were combined and used as end-point diagnostic methods (termed REPORT) to detect G. duodenalis assemblage A and B. The diagnostic results can be observed by fluorescence readouts with the naked eye under blue light or colorimetric signals using a lateral flow strip (LFS). Results The limit of detection (LOD) of the REPORT‑based G. duodenalis assemblage A detection was 2.04 CFU/ml and 10 trophozoites per gram (TPG), and the LOD of assemblage B was 1.1 CFU/ml and 10 cysts per gram (CPG). The REPORT‑based G. duodenalis assemblage A and assemblage B detection methods have strong specificity and no cross-reactivity with other assemblages of G. duodenalis or common enteric parasitic protozoa and have excellent performance in clinical sample detection. Conclusions This study presents a novel strategy for the direct identification of G. duodenalis assemblages A and B, requiring neither highly trained personnel nor costly specialized equipment. Graphical Abstract